Perioperative FLOT plus ramucirumab for resectable esophagogastric adenocarcinoma: A randomized phase II/III trial of the German AIO and Italian GOIM - Götze, Thorsten; Hofheinz, Ralf-Dieter; Gaiser, Timo; Schmalenberg, Harald; Strumberg, Dirk; Goekkurt, Eray; Angermeier, Stefan; Zander, Thomas; Kopp, Hans G.; Pink, Daniel; Siegler, Gabriele; Schenk, Michael; et al. (International journal of cancer, 2023)
This multicenter, randomized phase II/III study evaluated the addition of the vascular endothelial growth factor receptor-2 inhibitor ramucirumab to FLOT as perioperative treatment for resectable esophagogastric adenocarcinoma. Patients received either FLOT alone (Arm A) or combined with ramucirumab followed by ramucirumab monotherapy (Arm B). The primary endpoint for the phase II portion was the pathological complete or subtotal response (pCR/pSR) rate. Baseline characteristics were comparable between both arms with a high rate of tumors signet-ring cell component (A:47% B:43%). No between-arm difference in pCR/pSR rate was seen (A:29% B:26%), therefore the transition to phase III was not pursued. Nevertheless, the combination was associated with a significantly increased R0-resection rate compared with FLOT alone (A:82% B:96%; P = .009). In addition, the median disease-free survival was numerically improved in Arm B (A:21 months B:32 months, HR 0.75, P = 0.218), while the median overall survival was similar in both treatment arms (A:45 months B:46 months, HR 0.94, P = 0.803). Patients with Siewert type I tumors receiving transthoracic esophagectomy with intrathoracic anastomosis showed an increased risk of serious postoperative complications after ramucirumab treatment, therefore recruitment of those patients was stopped after the first-third of the study. Overall, surgical morbidity and mortality was comparable, whereas more non-surgical grade ≥ 3 adverse events were observed with the combination, especially anorexia (A:1% B:11%), hypertension (A:4% B:13%) and infections (A:19% B:33%). The combination of ramucirumab and FLOT as perioperative treatment shows efficacy signals, particularly in terms of R0 resection rates, for a study population with a high proportion of prognostically poor histological subtypes, and further evaluation in this subgroup seems warranted.
Online veröffentlicht: 8. März 2023
Gesehen am 19.08.2024